Implementation of Competency Selection Exams for PPPK on Computer-Assisted Tests at Universitas Sebelas Maret - Winarno Winarno; Bambang Harjito; Muhtar; Galih Akbar Moerbayaksa; Anas Falih Faishal (Warta LPM, 2026)
Customer satisfaction is crucial in a service, especially in the competency selection process based on the Computer Assisted Test (CAT). This selection process is integral to creating a professional and high-quality state bureaucracy. Background of the problem: Nevertheless, the extensive deployment of CAT in the public sector recruitment domain has frequently occurred without the concomitant execution of methodical assessments of participant satisfaction, especially in relation to service quality, system dependability, and uniformity among the various organizing entities;(2) Objectives: This study aims to evaluate the satisfaction of exam participants and related agencies regarding the implementation of CAT-based selection at UNS; (3) Methods: The evaluation used a questionnaire consisting of 19 closed and one open question. The questionnaire was distributed to respondents, namely exam participants and the Regional Civil Service Agency, with a total of 920 respondents. The questionnaire contained key determining factors such as system quality, information, and service; (4) Results: The best agency based on this questionnaire was the service for the Pati Regency Government with a score of 3.73, and the lowest was the Karanganyar Regency Government with a score of 3.38. The customer satisfaction measurement results generally gave a score of 3.54; (5) Conclusion: The implementation of this activity was carried out very well. This is evident from the questionnaire responses, which received excellent ratings and (6) Recommendations or follow-up: It is recommended that forthcoming implementations of CAT enhance the standardization of services, prepare for technical assistance, and conduct ongoing assessments of participant satisfaction to ensure a more uniform and participant-focused examination process.